2020
DOI: 10.1128/jvi.01819-19
|View full text |Cite
|
Sign up to set email alerts
|

Integrin β1 Promotes Peripheral Entry by Rabies Virus

Abstract: Rabies virus (RABV) is a widespread pathogen that causes fatal disease in humans and animals. It has been suggested that multiple host factors are involved in RABV host entry. Here, we showed that RABV uses integrin β1 (ITGB1) for cellular entry. RABV infection was drastically decreased after ITGB1 short interfering RNA knockdown and moderately increased after ITGB1 overexpression in cells. ITGB1 directly interacts with RABV glycoprotein. Upon infection, ITGB1 is internalized into cells and transported to late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…In the current study, we analyzed the proteinprotein interactions between the RV-G protein and ITGB1 in different species (Figures 3A-C). Results obtained from ITGB1 and RV-G protein docking are consistent with previous studies which identified that the interaction site between ITGB1 and RV-G protein within residues 1-728 a.a on the ITGB1 ectodomain (Shuai et al, 2019). Also, our analysis showed that the G protein ectodomain was the interacting site with ITGB1 in human, dog, and bat.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the current study, we analyzed the proteinprotein interactions between the RV-G protein and ITGB1 in different species (Figures 3A-C). Results obtained from ITGB1 and RV-G protein docking are consistent with previous studies which identified that the interaction site between ITGB1 and RV-G protein within residues 1-728 a.a on the ITGB1 ectodomain (Shuai et al, 2019). Also, our analysis showed that the G protein ectodomain was the interacting site with ITGB1 in human, dog, and bat.…”
Section: Discussionsupporting
confidence: 91%
“…Both dog and black fruit bat showed nine a.a. residue difference in the tail domain relative to human. The differences in these residues (1-728 a.a) may be crucial, since the ITGB1 ectodomain constitutes the interaction site with the RV-G protein, as was pointed out in a previous study (Shuai et al, 2019). Our results highlight the sequence homology within the mGluR2 protein alignment among the different species (Figure 2B).…”
Section: Protein Sequence Alignmentsupporting
confidence: 77%
“…It also remains to be demonstrated whether viral entry through different receptors is context dependent. Another CSP Integrin β1 encoded by ITGB1 was recently shown to be required for the entry of rabies virus ( Shuai et al., 2020 ). Whether ITGB1 could also promote the entry of SARS-CoV-2 is another question that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is plausible that under certain physiological conditions when SARS-CoV-2 does not engage with the ACE2 receptor for its entry into the cell, PHB serves as an alternative receptor. Another CSP Integrin β1 encoded by ITGB1 was recently shown to be required for the entry of Rabies Virus 57 Whether ITGB1 could also promote the entry of SARS-CoV-2 is another question that needs to be addressed. MEPCE is another important enzyme involved in RNA stabilization by capping the 5’ end of RNA with methyl phosphate 58 .…”
Section: Discussionmentioning
confidence: 99%